GESTÃO DEMOCRÁTICA PARTICIPATIVA: A LEGISLAÇÃO SOBRE IMPLANTAÇÃO DE CONSELHOS ESCOLARES EM MUNICÍPIOS SUL-MATO-GROSSENSES - JULIA IRIGARAY CAMARGO (2022)
This study is part of the research line “History, Politics, Education” of the Graduate Program in Education – PPEGDU/FAED of the Federal University of Mato Grosso do Sul (UFMS), Campo Grande campus. The research entitled "Participatory Democratic Management: the legislation on the implementation of school councils in municipalities in the south of Mato Grosso do Sul" aims to analyze the regulation of the process of implementation of school councils in municipal education networks in the state of Mato Grosso do Sul. This analysis considers the principle of democratic management in education legislation and politics. The theoretical framework used is based on the following authors who deal with democratic management and the school council: Paro (2015; 2016; 2020), Mendonça (2000; 2001) , Wood (2011), Cunha (1991), Medeiros and Luce (2006), Souza (2021; 2009); Dourado (2007), Hora (2004), among other authors that support this research. bibliographic and documental analysis. The research on the implementation of school councils in the state of Mato Grosso do Sul was carried out in regulations from 14 (fourteen) municipalities in the state. The results of the analyzes indicate that these municipalities implemented school councils between 1997 and 2018, and these regulations are explained in legal instruments of different categories (laws, decrees, resolutions). It was also found that these laws established the functions of school councils, their composition, norms for the election of councilors and the attributions of this collegiate. These regulations contributed so that these municipalities, with the implementation of school councils, could begin their process of implementing the exercise of democratic management in municipal public schools. Keywords: Democratic management. School Council. National Program for Strengthening School Councils. Municipal Education Plans.